Desain instalasi pengolah limbah WC komunal masyarakat pinggir sungai desa Lingkar Kampus - Asep Sapei; M. Yanuar J. Purwanto; . Sutoyo; Allen Kurniawan (Jurnal Ilmu Pertanian Indonesia, 2011)
Cangkurawok Village is located in the outer of the Bogor Agricultural University area and does not have good sanitation facilities. Disposal of domestic wastewater directly discharges into drainage channels to river. Wastewater treatment plant design from toilets communal divides into three stages. The first stage is determining the location of toilets communal and excreta treatment plant. Location provided by the public is around 5 meters above the surface of the river water. The second stage is the determination of service areas. In this village consists of 70 heads of households as the basic criteria for determining the volume of septic tanks. The last step is determining the design of toilets communal and wastewater treatment unit. This stage requires t he unit options that fits on the selected sites, based on ease of maintenance and no need employ trained operators. Waste treatment facility consists septic tank and infiltration well planning. Septic tank volume is 26.5 m3 with the long dimension of 2.75 m, width of 5.5 m and height of 1.5 m plus 0.3 meters for free board. Septic tank serving four toilets communal is built above it, with the division of space for two men and two spaces for women. infi lt rat ion well constructed to absorb the waste liquid vertically through the soil pores. Layers of sand and gravel is spread throughout the wells to assist the flow pattern. Depth and diameter of infiltration well are 3 m and 1 rn, This wells should be placed lower than the drinking water sources and wells, with a minimum distance of 15 m.